Governance for the Environment - Young, Oran R. (Cambridge University, 2013)
This book is a product of our collaboration in the unique setting of the Donald Bren School of Environmental Science and Management at the University of California (Santa Barbara). Unlike mainstream, disciplinebased departments, which often create barriers to collaboration across the boundaries of established disciplines, the Bren School facilitates and actually encourages such collaborative efforts. So, first and foremost, we are grateful to the School for providing an academic setting conducive to our work on new developments in understanding both the nature and the role of governance in various realms.